PROFILAKTIKA INSPEKTORINING YASHASH MANZILLARIDAN UZOQ MUDDATGA KETGAN SHAXSLAR BILAN ISHLASH FAOLIYATI - Xasanov Xurshid Jamol o`g`li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
In this dissertation the concept, significance, criminological description, features of the work of the inspector of prevention with citizens who have returned from abroad for a long time, as well as the analysis of norms governing the work with citizens who have returned from abroad for a long time, a number ofproposals for working with citizens who have returned to their home countries for a long time from their place of residence, as well as the experience of advanced foreign countries in this area and their implementation in practice.